2008
DOI: 10.1053/j.gastro.2008.03.039
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Estrogen With and Without Progestin and Obesity on Symptomatic Gastroesophageal Reflux

Abstract: Background & Aims-An association between female hormones and symptomatic gastroesophageal reflux disease (GERD) and may be modified by obesity is suggested but not proven. Factors affecting GERD progression, however, are largely unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
2
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 33 publications
2
21
2
2
Order By: Relevance
“…However, it is interesting that the incidence and spontaneous loss of GORS were influenced by age, particularly for women. Postmenopausal hormone replacement therapy seems to be a risk factor for GORS and may to some extent contribute to this pattern for women 14 24. The substantial loss of GORS, not due to antireflux medication, found in the present study, is partly conflicting with the presumed chronic character of GORS and the large use of regular antireflux medication in this population.…”
Section: Discussioncontrasting
confidence: 82%
“…However, it is interesting that the incidence and spontaneous loss of GORS were influenced by age, particularly for women. Postmenopausal hormone replacement therapy seems to be a risk factor for GORS and may to some extent contribute to this pattern for women 14 24. The substantial loss of GORS, not due to antireflux medication, found in the present study, is partly conflicting with the presumed chronic character of GORS and the large use of regular antireflux medication in this population.…”
Section: Discussioncontrasting
confidence: 82%
“…A study has also suggested a positive association between physical activity at work and GERD symptoms but an inverse association with recreational physical activity [84]. In our study, the associations between occupational physical activity and frequency or severity of GERD symptoms were mixed.…”
Section: Discussioncontrasting
confidence: 45%
“…Initially, when the women with GERD symptoms who received conjugated estrogen treatment and a placebo were compared, estrogen therapy was not shown to affect the severity of existing symptoms. When the patients receiving conjugated estrogen+medroxyprogesterone and a placebo were compared, no increase was observed in the incidence of symptomatic GERD (2.4% for both) or in the severity and frequency of existing symptoms (18). In another retrospective cohort study, the relative risk was investigated for the use of PPIs or for GERD in women who used HRT (n=22101) and did not use HRT (n=29081); when multiple regression analysis was performed, a significant association was found between estrogen monotherapy and GERD risk (OR: 1.49, 95% CI 1.18-1.89, p<0.001).…”
Section: Hormone Replacement Therapy and Oral Contraceptive Drugsmentioning
confidence: 95%
“…In a randomized controlled study in which a to- Inducing/Facilitating Esophageal Inflammation&Damage tal of 40 centers participated, conjugated estrogen was given to 5310 of 10739 women who underwent postmenopausal hysterectomy, and a placebo was given to the remaining 5429 women; conjugated estrogen + medroxyprogesterone was given to 8506 of 16608 women who did not undergo hysterectomy, and a placebo was given to the remaining 8102 women. One year later, the subjects were evaluated in terms of the incidence of GERD symptoms and the progression of GERD (18). The incidence of new, moderate, and severe symptomatic GERD development was found to be slightly higher in the conjugated estrogen group in comparison to the placebo group (4.2% vs. 3.1%, OR: 1.35, 95% CI 0.99-1.85).…”
Section: Hormone Replacement Therapy and Oral Contraceptive Drugsmentioning
confidence: 99%